APLIKASI SPIRITUAL CARE MEMPERBAIKI RESPON SUBJEKTIF DAN OBJEKTIF PADA PASIEN INFARK MIOKARD AKUT DI RUANG ICU RSUD SYARIFAH AMBAMI RATO EBHU BANGKALAN - Faisal amir (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2019)
Acute myocardial infarction is a conditionof heart muscle necrosis due to an imbalance ofoxygen supply which almost always occurs due toa total blockage of the coronary artery bythrombus in unstable atherosclerosis (Robbin,2007 ; Kumar, et al. 2015). The purpose of thisstudy was to determine the effect of spiritual carein improving vascular response in patients withacute myocardial infarction This study was a Pre-ExperimentalAnalysis with One Group Pre Test-Post TestDesign. The population was 28 patients with AMIin the ICU Syarifah Ambami Rato Ebu BangkalanHospital and a sample of 17 patients taken bysimple random sampling technique. Therespondent filled out the cardiovascular functionquestionnaire at first. Then they were asked tolisten the asmaul husna for 10-15 minutes 3 timesa day; every morning, afternoon and night beforegoing bed. As a post test, the respondent filledquestionnaires after treatment. The results of study showed us the significant value by Wilcoxontest was ᾳ ≤ 0.05. Spiritual care can significantly improve thesubjective response of AMI patients with p value(0.001) < 0.05 and improve the objective responsewith p value (0.024) <0.05. Spiritual care improvesstress perception and stress response so that itcan regulate subjective and objective responsesin patients with acute myocardial infarction in theICU Syarifah Ambami Hospital Rato EbuBangkalan.